Utilization of Microvisco-Amylograph to Study Flour, Dough, and Bread Qualities of Hydrocolloid/Flour Blends. Issue 3 (3rd March 2016) - Hammed, Ademola Monsur; Ozsisli, Bahri; Simsek, Senay
Abstract : Changes in functionality of wheat flour blended with hydrocolloids (alginate, locust bean gum, guar gum, and xanthan) were investigated. Microvisco-amylograph and flour quality analyses were conducted and showed significant ( p < 0.05) differences among samples. Correlation of microvisco-amylograph values with other parameters showed that microvisco-amylograph parameters (final viscosity, setback, breakdown, etc.) showed significant ( p < 0.05) correlation with other parameters. Microvisco-amylograph breakdown was significantly ( p < 0.05) and positively correlated with dough strength and loaf volume. Microvisco-amylograph end of cooling, final viscosity, setback, and breakdown were identified as valuable for determination of flour, dough, and bread qualities as impacted by addition of hydrocolloids.